Dosimetric changes achieved and changes in target and parotid volumes in patients undergoing adaptive planning during chemoradiation therapy with helical delivery of treatment. Issue 4 (3rd December 2019) - Cummings, Michael A.; Youn, Paul; Abu-Aita, Rami; Herman, Amy; Hare, Mary Z.; Zhang, Hong; Chen, Yuhchyau; Singh, Deepinder P.
Abstract: Aim: Re-planning mid-treatment, with the adjustment of target volumes, has been performed as part of the normal workflow at our institution. We sought to quantify the benefit of this approach and identify factors to optimise plan adaptive strategies. Materials and methods: Patients with locally advanced oropharyngeal cancer treated to 70 Gy with concurrent chemoradiation (CCRT) on TomoTherapy® who underwent re-planning during the treatment were eligible. Survival and prognostic factors were evaluated with Kaplan–Meier and Cox proportional hazards, two-side p -value <0·05 significant. Results: Forty-two patients were identified with Stage III ( n = 5), IVA ( n = 34) and IVB ( n = 3) [AJCC 7 th ] disease. Median re-planning dose was 40 Gy (14–60 Gy). Median change in mean total parotid dose was reduction of 1 Gy (range –7·5 Gy to +13·9 Gy). The volume of PTV70 and PTV60 receiving 99% of the prescribed (V99) dose was increased by 2·2% (–3·3 to +16·6%) and 1·9% (–11·5 to +12·6%) by re-planning. As a continuous variable, increasing per cent nodal regression was associated with the improved disease control in a multivariate model including stage, pack years smoking and human papilloma viral (HPV) status (HR: 0·85, 0·71–0·99, p = 0·05). Findings: Adaptive planning generates a superior plan for the majority of patients, but there is modest overall parotid gland sparing.